The usage of music on physical training lessons among conservatoire students. - Кravchenko Oleg (Kharkov National Pedagogical University, 2011)
The article reveals the peculiarities of musical background during the physical training lessons. The students of Dnipropetrovsk Glinka Conservatoire took part in the experiment. The music was used in two forms - receptive and active. The methods of vocal-therapy and music-therapy were used. It was ascertained that the usage of music during the lessons of physical training among conservatoire students activates creative abilities, increases emotional mood and capacity for work and essentially improves the students` physical health.